2016
DOI: 10.1159/000454879
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and Differences in Autoimmune Hepatitis Epidemiology between East and West: Autoimmune Hepatitis in East Asia, Southeast Asia, and South Asia

Abstract: Background: Autoimmune hepatitis (AIH)is a relatively rare disease that can develop regardless of age or ethnicity. However, its clinical features differ between eastern and western populations due to several heterogeneous genetic and environmental factors. We herein report the clinical characteristics of AIH patients in East Asia, Southeast Asia, and South Asia. Summary and Key Messages: The prevalence of AIH in eastern countries is considered to be lower than in western countries. Although a few young patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 58 publications
0
14
0
1
Order By: Relevance
“…It is interesting to note that the incidence and prevalence of AIH are consistently reported as lower in the East than in the West as summarized by Enomoto et al [6] . In the West, the prevalence of AIH was reported as 15-25 cases per 100,000 inhabitants, whereas much lower rates of 4-5 cases per 100,000 inhabitants were reported in the East [9] .…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…It is interesting to note that the incidence and prevalence of AIH are consistently reported as lower in the East than in the West as summarized by Enomoto et al [6] . In the West, the prevalence of AIH was reported as 15-25 cases per 100,000 inhabitants, whereas much lower rates of 4-5 cases per 100,000 inhabitants were reported in the East [9] .…”
mentioning
confidence: 93%
“…The current working model postulates that environmental triggers, a failure of immune tolerance mechanisms, and a genetic predisposition collaborate to induce an uninhibited T cell-mediated immune attack upon hepatocytes [5] . In this issue, Enomoto et al [6] have provided an excellent summary of the similarities and differences in the epidemiology of AIH between the East and the West.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This may be partly due to the wide spectrum of clinical presentation and lack of specific biomarkers and simple diagnostic criteria. Recently, several researches demonstrated that the incidence and prevalence of AIH were increasing, not only in Europe and Northern America but also in some Asian countries . A systematic review on the incidence of AIH published in 2015 described AIH occurrence all over the world but did not conduct a meta‐analysis .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several researches demonstrated that the incidence and prevalence of AIH were increasing, [9][10][11][12] not only in Europe and Northern America 9,11,12 but also in some Asian countries. 10,13 A systematic review on the incidence of AIH published in 2015 described AIH occurrence all over the world but did not conduct a meta-analysis. 14 Therefore, in this study, we conducted a systematic review and meta-analysis with the aim to pool the global incidence and prevalence rate of AIH and characterize the population difference.…”
Section: Introductionmentioning
confidence: 99%